2014
DOI: 10.1371/journal.pone.0092007
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Induces the Apoptosis and Regulates MAPK Signaling Pathways in Mouse Macrophage ANA-1 Cells

Abstract: Apigenin is a naturally occurring plant flavonoid that possesses antioxidant, anti-cancer and anti-inflammatory properties. However, there are few reports has been done on the ability of apigenin to induce apoptosis in macrophages. In this study, mouse macrophage ANA-1 cells were incubated with different concentrations of apigenin. The cell viability was determined by an MTT assay. The cell apoptosis were analyzed by flow cytometric analysis. Apoptosis were also analyzed using a TUNEL assay and a DNA ladder. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…The intensity of the bands was quantified using Quantity One software. OIM osteogenicinduced medium; **p \ 0.01 regulated MAPK signaling pathways [26,27]. Thus, we explored the role of JNK and p38 MAPK pathway in the apigenin-mediated regulation of osteogenic differentiation in hMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the bands was quantified using Quantity One software. OIM osteogenicinduced medium; **p \ 0.01 regulated MAPK signaling pathways [26,27]. Thus, we explored the role of JNK and p38 MAPK pathway in the apigenin-mediated regulation of osteogenic differentiation in hMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin was reported to induce apoptosis in mouse macrophage ANA-1 cells and increase melanogenesis in B16 cells via regulating the MAPK pathways [26,27]. Although some studies showed that MAPK pathways were involved in bone formation [28][29][30], the effect of apigenin on bone formation via MAPK pathways is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells, apigenin provides a protective effect against LPS-induced inflammation by decreasing caspase-3 activation and modulating mitochondrial function (11). Apigenin exerts anti-inflammatory activity via multiple mechanisms (12), including the induction of apoptosis and the regulation of MAPK signaling pathways in mouse macrophage ANA-1 cells (13). Other mechanisms include the inhibition of inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Different size, number, and shape of the mitochondria as well as different structure and genomic alterations have been reported in cancerous cells compared to normal cells. In addition, frangibility of the mitochondria in liver cancer cells has been reported by some researchers (29,30).…”
Section: Discussionmentioning
confidence: 85%